Exploring Items and Developing Instrument for Measuring Organizational Performance among Small Medium Enterprises in Jordan - Dehisat, Manal Mustafa; Awang, Zainudin (International Review of Management and Marketing, 2020)
This paper explored the reliability of an instrument to evaluate organizational performance (OP) of the SMEs sector in Jordan employing Exploratory Factor Analysis (EFA). The paper used EFA and is different from other studies with regard to Total Quality Management (TQM) practice as a mediator between Entrepreneurial characteristics and OP. We applied cross-sectional study design, and data collection was from a proportionate Stratified Sampling with 100 questionnaires distributed to managers or owners of Jordanian SMEs grouped by industry type (food industry, machinery/equipment, and paper manufacturing). We verified the consistency of the instrument which contained 10 items for each one of the constructs. The researchers employed Cronbach’s Alpha to verify the internal reliability of the current instrument and confirmed that it was reliable. This paper provides a detailed explanation of the procedures for conducting the EFA on Organizational Performance. The outcomes of this study would benefit those involved in future research related to Organizational Performance. Keywords: Exploratory Factor Analysis, Entrepreneurial Characteristics, TQM Practices, Organizational Performance JEL Classifications: L2, L3 DOI: https://doi.org/10.32479/irmm.10531